NeighborNet: improved algorithms and implementation - Bryant, David; Huson, Daniel H. (Frontiers in Bioinformatics, 2023)
NeighborNet constructs phylogenetic networks to visualize distance data. It is a popular method used in a wide range of applications. While several papers investigate its mathematical features, here we focus on computational aspects. The algorithm operates in three steps. We present a new simplified formulation of the first step, which aims at computing a circular ordering. We provide the first technical description of the second step, the estimation of split weights. We review the third step, constructing and drawing the network. Finally, we discuss how the networks might best be interpreted, review related approaches and present some open questions.